Optical external efficiency calculation for mid-infrared quantum cascade laser - Hamadou, Abdelouahab (Oficyna Wydawnicza Politechniki Wrocławskiej, 2011)
In this paper, we present a simple method for calculation of optical external efficiency of mid-infrared quantum cascade laser. The approach is based on the three-level rate equations describing the variation of the electron number in the excited states and the photon number present within the cavity. We have obtained a simple analytical formula for the optical external efficiency. The effects of cavity lengths and current injection are taken into account. It has been found that the optical external efficiency becomes more important at high current injection and at lower cavity lengths.
Optica Applicata, Vol. 41, 2011, Nr 3, s. 717-725
Keywords: optyka; quantum cascade laser; rate equations; output power; optical external efficiency